2022
DOI: 10.48550/arxiv.2201.07773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extragalactic fast X-ray transient candidates discovered by Chandra (2000-2014)

J. Quirola-Vasquez,
F. E. Bauer,
P. G. Jonker
et al.

Abstract: Context. Extragalactic Fast X-ray Transients (FXRTs) are short flashes of X-ray photons spanning a few seconds to hours, with an uncertain origin. Aims. Our ignorance about their physical mechanisms and progenitor systems is due in part to the lack of clear multi-wavelength counterparts in most cases,because they only have been identified serendipitously. Methods. We develop a systematic search of FXRTs using a straightforward X-ray flare search algorithm, in the Chandra Source Catalog (Data Release 2.0; 169.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 164 publications
(322 reference statements)
0
2
0
Order By: Relevance
“…Indeed, it has been suggested that a population of orphan extended emission bursts should also be present [30,31]. Furthermore, there are claims that a population of fast X-ray transients seen in narrow field X-ray observations (e.g with Chandra) arise from compact object mergers [92,93]. None of these systems show initial short spikes (albeit in a much softer energy band than the Swift-BAT).…”
Section: Compact Object Mergersmentioning
confidence: 99%
“…Indeed, it has been suggested that a population of orphan extended emission bursts should also be present [30,31]. Furthermore, there are claims that a population of fast X-ray transients seen in narrow field X-ray observations (e.g with Chandra) arise from compact object mergers [92,93]. None of these systems show initial short spikes (albeit in a much softer energy band than the Swift-BAT).…”
Section: Compact Object Mergersmentioning
confidence: 99%
“…Indeed, it has been suggested that a population of orphan extended emission bursts should also be present [30,31]. Furthermore, there are claims that a population of fast X-ray transients seen in narrow field X-ray observations (e.g with Chandra) arise from compact object mergers [92,93].…”
Section: Compact Object Mergersmentioning
confidence: 99%